Web Service Scheduling in Multi-Cloud Environment - Sen, P; Sarddar, D; Sinha, S.K; Pandit, R (International Journal of Computer Sciences and Engineering, 2019)
Cloud platforms are increasingly being used for hosting a broad diversity of services from traditional ecommerce applications to interactive web-based IDEs. However, we have noticed that the proliferation of offers by service providers promotes several challenges. Developers have to consider migrating services from one cloud to another and manage distributed applications spanning multiple clouds while specific service is not available in single cloud. In this paper, we have introduced a new methodology of web services scheduling in multi-cloud environment based on the request of preferred user services in different time slots of the day. A comparison has been made on the performance and cost of single and multi-cloud environments to show how multi-cloud is more efficient than single cloud and also to conclude that web service scheduling in multi-cloud environment is more efficient than single cloud during service migration.